The Influence of the Hybrid Compound Nd(NO3)3@Zn-MOF on the Growth of Vanilla (Vanilla planifolia Jacks. ex Andrews) Cultured In Vitro: A Preliminary Study - Carlos Alberto Cruz-Cruz; Xóchitl De Jesús García-Zárate; José Luis Spinoso-Castillo; Rodolfo Peña-Rodríguez; Raúl Colorado-Peralta; Ricardo Sánchez-Páez; Jericó Jabín Bello-Bello (Agronomy)
Hybrid compounds have a significant impact on agriculture as slow macro- and micronutrient administration systems. This study aimed to evaluate the synthesis and effect of the hybrid compound Nd(NO3)3@Zn-MOF in different concentrations on the in vitro growth of vanilla (Vanilla planifolia Jacks. ex Andrews). A total of 13 vanilla plantlets per treatment were cultivated in test tubes with semi-solid Murashige and Skoog (MS) medium and without growth regulators and treated with 0, 5, 10, 15, and 30 mg L−1 of Nd(NO3)3@Zn-MOF. After 60 days of culture, we evaluated different morphological and biochemical parameters, such as shoot length, root length, the number of roots, the number of leaves, total chlorophyll and carotenoid content, antioxidant capacity, and phenolic compound content. Our results showed that the Nd(NO3)3@Zn-MOF at 10 mg L−1 concentration increased plantlet length. Furthermore, we observed an increase in root length and number with the 5 and 10 mg L−1 concentrations, and a decrease in these same parameters with the 15 and 30 mg L−1 Nd(NO3)3@Zn-MOF concentrations. There were no significant differences regarding the number of leaves or total chlorophyll content. As for the antioxidant capacity, we observed an increase with 5, 10, and 15 mg L−1 of Nd(NO3)3@Zn-MOF and a decrease with the highest concentration. Finally, the phenolic and carotenoid content decreased with the 15 and 30 mg L−1 Nd(NO3)3@Zn-MOF concentrations compared to the control. In conclusion, the hybrid compound Nd(NO3)3@Zn-MOF showed beneficial effects on the growth, physiology, and biochemistry of V. planifolia in vitro when plants were treated at low concentrations. Additionally, the high concentrations used in this study did not induce toxicity. Our findings suggest that Nd(NO3)3@Zn-MOF could be used as a biostimulant in vanilla during its in vitro culture. However, due to the hormetic effect and the possible different reactions of different genotypes, this requires further detailed research.